EFFECT OF SOME ENVIR0NMENTAL FACTORS ON T ACUTE TOXICITY OF DELTAMETHRIN TO COMMON CARP: A LAB0RATORY STUDY UNDER AEROBIC CONDITION - Kent, Yhunsenlo; Datta, Subhendu; Shah, Parvez Sazad; Das, Radha C. (Journal of Indian Fisheries Association, 2015)
The toxicity of xenobiotics in aquatic ecosystems is influenced by manyfactors such as ambient temperature, water hardness, pond soil type, etc. Inthe present study, it was observed that air temperature, water hardness andsoil sediment have profound influence on the toxicity of deltamethrin tocommon carp fry (ay. length 3.5 ± 0.5 cm, ay. weight 0.58 ± 0.25 g); 96h LC50values for common carp at 38.07 ± 2.20° C maximum and 27.86 ± 1.22°C minimumair temperature in soft and very hard water were 0.102 and 0.495 jig 1 .1 ,respectively. This value had increased significantly to 2.37 and 3.02 jig Pat30.55 ± 1.21° C maximum and 26.04 ± 0.61° C minimum air temperature,respectively. When sediment was included, 96h LC 50 at 38.07° C maximumtemperature in very hard water was 1.808 lig 1' and this had increased to8.073 jig 1-1 when tested at 30.55° C maximum temperature. Due to the 7.5° Cincrease in maximum and 1.7° C in minimum temperature, toxicity increasedsignificantly. Lower toxicity in very hard water in comparison to soft watermay be due to the lower solubility of deltarnethrin and high level of calcium.Adsorption reaction of deltamethrin with clay, humus, FeOOH, MnOOH andparticulate organic carbon, and complexation reaction with dissolved organiccarbon were responsible for the lowered toxicity in the experiment withsediment. Exposure time had no significant effect on acute toxicity ofdeltamethrin.Keywords: Deltamethrin, common carp, temperature, water hardness, sediment